Integration Between Artificial Intelligence and Cyber Security Technologies and Its Impact on Administrative Decisions - Sadeq Dhahir Farhan Alzaidi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research aims to understand the impact of the integration between artificial intelligence (AI) technologies and cyber security on administrative decisions in three aspects: (1) decision-making speed, (2) decision accuracy, and (3) decision effectiveness. A sample of 150 employees was drawn, and a survey was used to gather the required information. Data analysis was conducted using the statistical program SPSS 25, employing various statistical methods such as mean, standard deviation, correlation coefficient, and simple linear regression. The research concluded with several findings, the most important being: The integration of AI technologies and cyber security leads to improved speed, accuracy, and effectiveness of administrative decisions, The researcher recommended that institutions adopt AI technologies to enhance their cyber security systems, particularly in areas like machine learning and big data analysis.